Experimental Investigation on Effect of Fin Height on Microscale Heat Transfer and Fluid Flow for Macro Scale Industrial Applications - Cheng, Kai Xian (2017)
Microchannel for macro geometry application is gaining popularity particularly in aerospace, biomedical and photovoltaic. A novel method of employing microchannel in macro geometry at lower cost using conventional machining methods has been developed. A solid cylinder on outer diameter 19.4 mm is placed concentrically into a copper pipe of inner diameter 20 mm, forming an annular microchannel with 300 μm gap. This study takes a step further by introducing surface profile of different heights on the surface of solid cylinder and investigating the effect on two main design objectives- increasing heat removal capability at same pumping power and reducing pumping power for the same heat removal duty. Four surface profiles -parallel fins as well as fins with height of 0.1, 0.2 and 0.3 mm, were investigated experimentally at constant heat flux at Reynolds number from 690 to 4600. The amount of fluid in the microchannel, channel length of 30 mm, bifurcating angle of 75 degrees and mean hydraulic diameter of 600 μm are kept as constant parameters. A plain insert is used as benchmark for comparison of enhancement. In this study, insert with fins of 0.3 mm attains the highest enhancement of 43 percent increment in heat transfer as compared to plain insert using the same pumping power. While keeping the heat removal duty constant, the same insert is able to perform the duty using less than 50 percent the pumping power required by the plain insert at low Reynolds numbers.